China's national production function since 1997: A reinvestigation - Yanyuan Zhu; Xiao Feng (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2014)
We build China's national production function based on national accounting data since 1997, when China primarily transformed from the Planned economy to Market. By proxying and measuring stocks of human capital(HC), physical capital and the efficiency units, as well as government expenditure reflecting total factor productivity(TFP), we analyze CES production functions' explanation effects by numerical simulation, and then according to the findings, choose Cobb-Douglas form for further research. Our results include, first, Cobb-Douglas production function in the form of capital coefficients - capital relative density, appropriately reflects Chinaâs recent input-output relationship. Second, taking factor-augmenting technical progress into consideration, the proxy settings for two capitals are empirically plausible for future research on Chinaâs endogenous growth model. Third, expansionary government expenditure negatively affects Chinaâs TFP and output.
Keywords: C52; E01; O47; O53; 330; national production function; factor-augmenting technical progress; physical capital efficiency units